2011
DOI: 10.1007/s10508-011-9874-6
|View full text |Cite
|
Sign up to set email alerts
|

Do Women Pretend Orgasm to Retain a Mate?

Abstract: The current study tested the hypothesis that women pretend orgasm as part of a broader strategy of mate retention. We obtained self-report data from 453 heterosexual women (M age, 21.8 years) in a long-term relationship (M length, 32.8 months) drawn from universities and surrounding communities in the southeastern United States. The results indicated that (1) women who perceived higher risk of partner infidelity were more likely to report pretending orgasm, (2) women who reported greater likelihood of pretendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 14 publications
1
45
4
2
Order By: Relevance
“…One of the times to engage in mate retention, then, is when there is a perceived risk of partner infidelity Caton, Redlick, & O'Shannessy, forthcoming;Starratt, Shackelford, Goetz, & McKibbin, 2007). Kaighobadi et al (2012) showed that women who pretend orgasm (a DAM; Denes et al, 2019;Horan & Booth-Butterfield, 2019) enact more cost-inflicting mate retention, and this association was mediated by the perceived risk of partner infidelity. They interpreted these findings such that pretending orgasm may be a form of mate retention used to thwart partner infidelity.…”
Section: Perceived Risk Of Partner Infidelitymentioning
confidence: 99%
“…One of the times to engage in mate retention, then, is when there is a perceived risk of partner infidelity Caton, Redlick, & O'Shannessy, forthcoming;Starratt, Shackelford, Goetz, & McKibbin, 2007). Kaighobadi et al (2012) showed that women who pretend orgasm (a DAM; Denes et al, 2019;Horan & Booth-Butterfield, 2019) enact more cost-inflicting mate retention, and this association was mediated by the perceived risk of partner infidelity. They interpreted these findings such that pretending orgasm may be a form of mate retention used to thwart partner infidelity.…”
Section: Perceived Risk Of Partner Infidelitymentioning
confidence: 99%
“…We predict that a person who is more satisfied than he or she perceives his or her partner to be perceives a greater risk of the partner's infidelity, and consequently performs more mate retention (especially Benefit‐Provisioning) behavior to increase the partner's satisfaction. Likewise, mate retention behavior is associated with sexual behaviors that influence relationship satisfaction, such as oral sex (Pham & Shackelford, ; Sela et al, ), copulation frequency (Barbaro, Pham, & Shackelford, 2015), and pretending orgasm (Kaighobadi, Shackelford, & Weekes‐Shackelford, ). Future research could explore perceived discrepancies in these behaviors and their relationships with mate retention discrepancy and mate value discrepancy.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…An online survey of over 3,000 women, found that 74% had faked an orgasm in their current or most recent relationship (Mialon, 2011). Finally, 53.9% of 453 young American women (mostly university students) agreed that they had 'pretended that you were having an orgasm when you really weren't' during sexual intercourse with their current partner (Kaighobadi, et al, 2012). Despite variations in questions about whether women had ever faked or had faked in their current relationship, and about faking during intercourse or other sexual activities, the figures suggest the practice is widespread.…”
Section: Faking It Happens a Lotmentioning
confidence: 99%
“…Wiederman suggested that this 'unexpected' finding could be explained by the idea that such women hold themselves to a higher standard of sexual performance and thus fake orgasm to 'compensate for perceived deficits in sexual responsiveness ' (1997: 138). Evolutionary psychologists explain individual differences in faking as part of a broader strategy of 'mate retention' in which access to 'good genes is assured by decreasing the 'likelihood of a male partner's infidelity or defection from the relationship', and by signalling her own pleasure and thus 'manipulating his commitment to the relationship' (Kaighobadi et al, 2012(Kaighobadi et al, : 1122 . In their questionnaire-based study of 453 young women (mostly students) in the US, Kaighobadi and colleagues found that women who perceived a greater risk that their partners would be unfaithful were more likely to fake orgasm.…”
Section: Why Do Women Fake?mentioning
confidence: 99%